Etiological Spectrum of Persistent Neonatal Jaundice - Muhammad Omer, Muhammad Omer (Journal of Rawalpindi Medical College, 2010)
Background:To determine the etiological spectrum of persistent neonatal jaundice, which persists for more than two weeks of a neonate’s life Methods: In this descriptive study 35 patients with persistent neonatal jaundice were included. History, presentation, symptoms, signs and diagnostic modalities to evaluate the causes of neonatal jaundice were assessed Results: Out of total 35 patients, 25 (71%) were found to be having conjugated hyperbilirubinaemia while only 10 (29%) had unconjugated variety. Idiopathic neonatal hepatitis (28%) and neonatal sepsis (22%) were the two major etiologies observed for persistent neonatal jaundice. 80% of survival rate was observed and the median age at which the jaundice was first noticed was determined to be 6.23+/-2.28 days. Median age of clinical clearance of jaundice in patients with neonatal sepsis was 25 +/- 9.2 days and in those with neonatal hepatitis 75 +/- 12.6 days. Conclusion: Cholestatic jaundice is a major cause of persistent neonatal hepatitis and idiopathic neonatal hepatitis accounts for the major bulk of these patients.